TV buying - Marshall, Jim (Henry Stewart Talks, 2009)
Market complexity, Level of accountability, Measure of impact and effectiveness, TV buying, The market, The TV buying process, Setting objectives, Negotiations, Managing the campaign, Results and reporting, Data and information systems
Archived at 2022/04/07